Urban Design Livable Community Strategies Towards Urban Parks And Green Spaces Indicator - Shukri, Sharyzee Mohmad; Singaram, Hema Sundari; Jamil, Mohd Azli Mohamad (MAJ - Malaysia Architectural Journal, 2024)
Urban Design Livable Community Strategies Towards Urban Parks And Green Spaces Indicator